How Digital Leadership Is(n't) Different - Kane, Gerald; Kane, Gerald (MIT Sloan Management Review, 2019)
Many of us assume that the leadership handbook must be completely rewritten for the digital age. Is this true? Or are we overly focused on what's changing and thus neglecting the fundamentals? There is something to be said for both arguments. While many core leadership skills remain the same, the demands of digital disruption call for certain new ones, as well. This article explores which are which and what we can learn from organizations that are digitally maturing.